Hervaeus Natalis’s Epistemology of Faith: A Reconstruction - Piché, David (Vivarium, 2025)
Besides his commentary on distinctions 23-25 of Book iii of the Sentences, Hervaeus Natalis deals with faith from the perspective of epistemology and philosophical psychology in two other texts: Quodlibet ii, q. 15, and Opinio de difficultatibus contra doctrinam fratris Thomae (or Defensio doctrinae fratris Thomae), both dating from his Parisian regency (1307-1309). This article reconstructs the doctrine of faith contained in these texts and examines it in its historical context.